Solving Mind-Body Issues Requires Combining Philosophical Reflection and Empirical Research - Kakkuri-Knuuttila, Marja-Liisa (Journal of NeuroPhilosophy, 2023)
This paper argues that to progress with philosophical issues concerning brain-mind relations one needs to combine philosophical reflection and empirical research with theoretical model building. Philosophy and abstract theorizing alone do not carry us far, as will be illustrated by analyzing the views about panpsychism by the quantum physicist David Bohm, who builds his reasoning on quantum mechanical analogies. His reflection around the notion of active information, adopted in his causal interpretation of quantum mechanics to replace the Newtonian notion of force, turns out to be a fallacy of equivocation. His other line of reasoning to specify matter-mind unity in terms of soma-significance and signa-somatic processes yields problems of its own. To illustrate empirical investigations on brain-mind relations, I shall present the tripartite model of the experiential selfhood and the related Self-Me-I index as proposed by the neuroscientists Fingelkurts and Fingelkurts, along with their background theory called operational architectonics (OA) of brain-mind functioning. The model states that the three components of selfhood, Self, Me, and I, correlate to three distinct operationally synchronized cortical areas, the frontal cortex, the right posterior cortex, and the left posterior cortex. The philosophical and practical benefits of their framework will be exemplified by presenting the results of a series of studies with the philosopher Tarja Kallio-Tamminen about the effects of meditation reflected in the Self-Me-I index.